Direction and distribution sensitivity of sup-DOF interference suppression for GNSS array antenna receiver - Sun, Yifan; Chen, Feiqiang; Wang, Feixue; Liu, Wenxiang; Li, Baiyu; Song, Jie (Frontiers in Physics, 2023)
Distributed wideband jamming (interference) is commonly used in navigation countermeasure. Due to the limited volume of GNSS (Global Navigation Satellite System) antenna array receiver, the number of interferences usually exceeds the number of array elements. At present, the anti-jamming capability and mechanism of GNSS array antenna against distributed sup-DOF (Degree of Freedom) interference have not been fully studied. To solve this problem, this paper analyzes the characteristics of GNSS array antenna against sup-DOF interference. Firstly, the definition of sup-DOF interference of GNSS array antenna is proposed from the perspective of spatial anti-jamming; Secondly, the directional characteristics of GNSS array antenna for sup-DOF interference suppression are analyzed. The results show that the performance of sup-DOF interference suppression is sensitive to the direction and distribution of interference. On the one hand, the residual interference power varies from interference direction and distribution, while the minimum value of which is zero and the maximum value is the sum of interference power. On the other hand, the suppression performance of UCA (Uniform Circular Array) and central UCA is periodic along azimuth. If the number of elements on the circumference is M(M≥3), the period of the suppression performance is . The conclusions of this paper show the upper and lower bounds of sup-DOF interference suppression performance and the variation rule in azimuth, which can be used in the fields such as interference deployment, anti-jamming performance evaluation and anti-jamming algorithm development.